State Religion and Corruption in Islamic Countries: An Empirical Examination - Arif Rahman Hakim; Putro Samudro (Universitas Islam Internasional Indonesia, 2025)
Corruption remains pervasive in many Islamic countries, despite the ethical values and integrity often associated with religious norms. This study investigates how state religion and proportion of Muslim population impacts corruption levels in member countries of the Organisation of Islamic Cooperation (OIC). Utilizing cross-sectional data from 53 OIC countries and employing the Ordinary Least Squares (OLS) regression method, the study finds that the percentage of the Muslim population has a negative but statistically weak effect on corruption. Conversely, the adoption of Islam as a state religion significantly increases corruption, suggesting that religious institutionalization may undermine governance quality. These results challenge prior assumptions that religiosity inherently reduces corruption. Instead, the study highlights that institutional frameworks, rather than religious adherence, shape governance outcomes. The findings underscore the need for anti-corruption efforts in Islamic countries to prioritize institutional reforms and economic policies that enhance transparency and accountability, rather than relying solely on religious values.